Adherence to prophylaxis and quality of life in children and adolescents with severe haemophilia A. (4th February 2015) - García‐Dasí, M.; Aznar, J. A.; Jiménez‐Yuste, V.; Altisent, C.; Bonanad, S.; Mingot, E.; Lucía, F.; Giménez, F.; López, M. Fernanda; Marco, P.; Pérez, R.; Fernández, M. Á.; et al.
Summary Treatment adherence in adolescents with chronic diseases is around 50%, and failure is more common in preventive therapy. In haemophilia, contradictory results are reported by the published studies. The objective of this study was to evaluate adherence with factor VIII (FVIII) prophylaxis in Spanish patients with severe haemophilia A between age 6 and 20 years. Data were collected retrosp‐ectively in the previous 2 years. The primary endpoint was the absolute adherence index (AAI), and the endpoints were related to clinical status, age, prophylaxis regimen, responsibility for factor administration and quality of life (QoL), assessed by the Haemo‐QoL questionnaires. A total of 78 patients from 14 Spanish hospitals were recruited. Adherence ranged between −64.4 and 66.7 (mean −3.08). No differences were observed between children and adolescents (7.11 vs. 6.39; P = 0.809). A statistically significant association (P < 0.010) between infra adherent group and target joint was found, as was a statistically significant difference (P < 0.010) between the number of bleeding episodes experienced by the adherent group (mean 1.4) and by infra adherents (mean 4.5). There was no significant difference between AAI and prophylactic regimen (6.35 vs. 6.96, P = 0.848), neither between AAI and the person responsible for factor administration (5.57 vs. 8.79, P = 0.326). The Haemo‐QoL scores (8–12 years) were related to adherence level (P < 0.05). Adherence was approximately ideal and patients perceived a high QoL. Because of the repercussions for compliance, it is essential to work during puberty on emotional and self‐acceptance aspects of the disease, as well as coping, and the patient's family, school and health team relationships.